Spontaneous Hemothorax by Pulmonary Arteriovenous Malformation during Pregnancy - Duan, Chuxiao; Mu, Yunfei; Yang, Yi (The Thoracic and Cardiovascular Surgeon Reports, 2023)
Background: Pulmonary arteriovenous malformation (PAVM) is a rare vascular malformation that may cause hemothorax, especially during pregnancy.Case Description: A 25-year-old woman presented sudden-onset left chest pain, dizziness, and dyspnea in the 27th week of gestation. Computed tomography angiography showed left pleural effusion with complete hemithorax opacification and an aneurysmal PAVM. She exhibited hemorrhagic shock and received emergency exploratory video-assisted thoracic surgery. A ruptured PAVM was identified and stopped by wedge resection in the upper lobe of the left lung. The patient's postoperative clinical course was uncomplicated. She subsequently delivered a healthy live baby vaginally at 41 weeks gestation.Conclusion: PAVM should be considered in pregnant women with hemothorax. Emergency thoracoscopic surgery is the best treatment option.
Keywords: pulmonary artery and vein; pregnancy; shock